Pengaruh Jogging Terhadap Kadar Gula Darah Puasa pada Penderita Diabetes Mellitus Tipe 2 - Santoso S. Kep., Ners M. Kep, Mochamad Budi; Irianto, Gunawan; Erik Tania, Yolanda (JURNAL KESEHATAN KARTIKA, 2022)
Background: Diabetes mellitus is a global public health problem. In Indonesia, the prevalence of diabetes mellitus is ranked 6th in the world after China, India, the United States, Brazil and Mexico, which is 10.3 million people (International Diabetes Federation, 2017). One of the pillars of diabetes mellitus is physical activity (sports) including jogging which has a very important role in controlling blood sugar levels. The purpose of this study was to determine the effect of physical exercise jogging on fasting blood sugar levels in pre-elderly people with Type 2 Diabetes Mellitus. Method: This study uses a "pre-experimental" design with a "One group pretest posttest" design. The number of samples as many as 11 people using purposive sampling technique. The intervention given was jogging which was done 3 times for 1 week. Analysis of the data used is the Paired T-test (t-test dependent). Result: The results showed that the average fasting blood sugar level before jogging was 167.55 mg/dl, and the average after jogging was 144.82 mg/dl. Statistical results obtained p value (0.001) < (0.05). Conclusion: it can be concluded that there is an effect of physical exercise jogging on fasting blood sugar levels in pre-elderly who suffer from Type 2 Diabetes Mellitus in the Work Area of ​​the South Cimahi Health Center. Researchers suggest that respondents who have participated in jogging can share their experiences with other Diabetic Mellitus respondents who have not been exposed to jogging, the implementation of jogging has been shown to reduce blood sugar levels within normal limits. Keyword: Diabetes, jogging, blood sugar level